Pengembangan Ensiklopedia Siklus Hidup Hewan Berbasis Discovery Learning - Ade Cita Geovani Cahya Ningtias; Wahid Ibnu Zaman; Ika Santia (Lembaga Yasin AlSys, 2026)
Although visual learning media and the Discovery Learning model have been widely used in elementary school science learning, the development of an illustrated mini-encyclopedia integrated with Discovery Learning on animal life cycle material remains limited. This study aims to develop a Discovery Learning-based illustrated mini-encyclopedia on animal life cycle material and to evaluate its level of validity, practicality, and effectiveness in improving the learning outcomes of third-grade elementary school students. This study used a research and development (R&D) method with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The study involved 29 third-grade students of SDN Mrican 2, consisting of 6 students in the limited trial and 23 students in the field trial. Data were collected through expert validation sheets, teacher and student response questionnaires, and learning outcome tests, and were then analyzed using descriptive percentages and N-Gain. The results showed that the illustrated mini-encyclopedia developed obtained a validity score of 84.40%, categorized as highly valid. Product practicality was indicated by a teacher response of 96%, student responses in the limited trial of 91.6%, and student responses in the field trial of 91.73%, all of which were categorized as highly practical. The product was also proven effective in improving students’ learning outcomes, as indicated by classical learning mastery of 100% and an N-Gain score of 0.75, categorized as high. These findings confirm that the integration of visual learning media with Discovery Learning can increase student engagement and learning outcomes in elementary school science learning. The implications of this study contribute to the development of Discovery Learning-based learning media and serve as a practical reference for teachers and schools in implementing innovative science learning resources.